2002
DOI: 10.1039/b202208g
|View full text |Cite
|
Sign up to set email alerts
|

Oriented crystallization of calcite single crystals grown underneath monolayers of tetracarboxyresorc[4]arenes

Abstract: 20-tetra(n-undecyl)resorc[4]arene, 1, and its Ca salt, 2, are described. Structural data were analyzed in terms of supramolecular packing motifs of the constituent amphiphilic macrocycles. Monolayer experiments indicate that a similar packing arrangement can be predicted for monolayers of 1 spread at the air-water interface. CaCO 3 (calcite) single crystals were grown underneath monolayers of 1 with highly uniform (012) orientation. This particular orientation was observed for a variety of structurally dissimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
2
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 33 publications
3
35
2
2
Order By: Relevance
“…16) [93][94][95]. However, in spite of these fundamental differences in molecular structure, crystallization assays employing monolayers of 14 gave (01.2) oriented calcite crystals that were virtually indistinguishable from those that grew beneath monolayers of 12 or 13.…”
Section: Influence Of Coordination Geometrymentioning
confidence: 82%
See 2 more Smart Citations
“…16) [93][94][95]. However, in spite of these fundamental differences in molecular structure, crystallization assays employing monolayers of 14 gave (01.2) oriented calcite crystals that were virtually indistinguishable from those that grew beneath monolayers of 12 or 13.…”
Section: Influence Of Coordination Geometrymentioning
confidence: 82%
“…Right: Structural formula of tetracarboxy-resorc [4]arene 14, which according to X-ray analytical investigations and NMR studies assumes a C 2v -symmetric boat conformation [95] In summary, the results of these investigations demonstrated that neither calixarene nor resorcarene derivatives have a tendency to form highly ordered liquid-crystalline phases during compression. Moreover, the growth of (01.2) oriented calcite crystals exclusively occurred at low surface pressure (π = 0.…”
Section: Scheme 5 Leftmentioning
confidence: 92%
See 1 more Smart Citation
“…Note that a well-developed, preferred orientation of the [012] type was also detected for synthetic calcite growth on monolayer templates consisting of alkanethiols terminated by COO -groups on a gold substrate, [34] or macromolecules of calixarenes and resorcarenes. [35,36] In order to explain anisotropic lattice distortions, we assume that the intracrystalline organic molecules are not just adhering to the specific crystal planes. Since these macromolecules are rich in aspartic and glutamic residues, [37] their COO -groups could coherently substitute some of the carbonate groups in the calcite structure.…”
mentioning
confidence: 99%
“…The so-called molecular recognition is assumed to facilitate the nucleation of calcite [9,37] alter the habit of the growing crystal [2,35,36] or trigger the crystallisation of a specific polymorph [8,10,38]. However, the postulated mechanism of epitaxial growth of calcium carbonate on macromolecular arrangements has been discussed critically recently [33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%